Hypothyroidism during neonatal and perinatal period induced by thyroidectomy of the mother causes depressive-like behavior in prepubertal rats - Marisol Pineda-Reynoso (Dove Medical Press, 2010)
Marisol Pineda-Reynoso, Edgar Cano-Europa, Vanessa Blas-Valdivia, Adelaida Hernandez-Garcia, Margarita Franco-Colin, Rocio Ortiz-ButronDepartamento de Fisiología ‘Mauricio Russek Berman,’ Escuela Nacional de Ciencias Biológicas, IPN, Carpio y Plan de Ayala, MéxicoAbstract: The objective of this study was to see if neonatal and perinatal hypothyroidism caused anxiety and depressive-like behaviors. Twenty female Wistar rats were randomly divided into two groups: 1) thyroidectomy caused hypothyroidism, in which the thyroid gland had been removed and the parathyroid reimplanted; and 2) false thyroidectomy. The thyroidectomy was made on rats anesthetized with ketamine-xylazine. The rats were mated and one day after giving birth, eight pups were assigned to each group randomly and they were distributed into two groups: a hypothyroid group containing male pups of a hypothyroid mother with a hypothyroid wet nurse; and a euthyroid group of male pups of a euthyroid mother with a euthyroid wet nurse. We analyzed the behavioral test at a prepubertal age. The neonatal and perinatal hypothyroidism caused by the mother’s thyroidectomy caused a decrease in body weight and length. We found that the neonatal and perinatal hypothyroidism enhanced the total exploratory activity without affecting social contact and the time spent in the open and closed arms in an elevated plus-maze. The hypothyroidism caused immobility without altering the lower climbing duration in the swimming test. This study shows a novel model to cause neonatal and perinatal hypothyroidism without using pharmacological drugs. We demonstrated that hypothyroid animals had a reduction in body weight and length, a retardation of neurodevelopment, and they had depressive-like behavior.Keywords: perinatal hypothyroidism, thyroidectomy, thyroid hormone, behavior, metabolism